Assessing the Awareness and Adoption of Biocompatible Dental Materials among Dental Practitioners: A Cross-Sectional Study - Shahzad, Aamir; Hasan, Sana Jalil; Khan, Azeem Gohar; Iqbal, Ayousha; Asif Shahzad, Muhammad; Mahboob, Musa (Journal of Neonatal Surgery, 2025)
Background: Biocompatible dental materials have gained increasing attention for their role in promoting patient safety and reducing adverse biological reactions. Despite global emphasis on biocompatibility, the extent of awareness and adoption among dental practitioners remains uncertain. Objective: To evaluate the level of awareness and adoption of biocompatible dental materials among dental practitioners and to identify factors influencing their clinical use. Methods: A descriptive cross-sectional study was conducted from January to June 2025 among 225 dental practitioners selected through convenience sampling from private clinics, academic institutions, and public hospitals. A pretested, structured questionnaire (Annexure I) comprising demographic details, awareness, and adoption-related items was distributed electronically and in person. Responses were coded and entered into Microsoft Excel, then analyzed using SPSS version 26. Associations between practitioner variables and adoption levels were examined using chi-square and t-tests. Multivariate logistic regression was applied to identify independent predictors of high adoption, reporting adjusted odds ratios (AOR) with 95% confidence intervals. Results: High awareness was observed in 60.9% of participants and high adoption in 52.9%. Significant predictors of adoption included high awareness (AOR = 2.95, p < 0.001), experience >5 years (AOR = 1.78, p = 0.03), and urban practice (AOR = 1.89, p = 0.04). High cost (40.4%) and limited availability (29.8%) were major barriers. Conclusion: Awareness, experience, and accessibility strongly influenced the adoption of biocompatible dental materials. Targeted education, cost reduction, and improved material availability are essential to enhance their routine clinical use.